2015
DOI: 10.1007/978-3-319-22822-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Strain Variation

Abstract: What is wild-type Epstein-Barr virus and are there genetic differences in EBV strains that contribute to some of the EBV-associated diseases? Recent progress in DNA sequencing has resulted in many new Epstein-Barr virus (EBV) genome sequences becoming available. EBV isolates worldwide can be grouped into type 1 and type 2, a classification based on the EBNA2 gene sequence. Type 1 transforms human B cells into lymphoblastoid cell lines much more efficiently than type 2 EBV and molecular mechanisms that may acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 157 publications
0
47
0
2
Order By: Relevance
“…The high incidence of some EBV-associated cancers in Asian populations, particularly NPC in Cantonese people, suggest a geographic variant that is in some way more oncogenic. The largest contributor to PC2 (2) was LMP1, and variation in LMP1 has been discussed extensively in relation to NPC and tumorigenicity in animal model systems (reviewed in reference 3). The high expression level of BART miRNAs in NPC and demonstration that BART miRNAs can mediate the tumorigenicity of EBV in an animal carcinoma model system (15) is also of interest, because part of PC2 was accounted for by variation in the BART miRNA cluster 2 region (2), which is part of the long pri-miRNA (primary miRNA) transcript from which BART miRNAs are processed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence of some EBV-associated cancers in Asian populations, particularly NPC in Cantonese people, suggest a geographic variant that is in some way more oncogenic. The largest contributor to PC2 (2) was LMP1, and variation in LMP1 has been discussed extensively in relation to NPC and tumorigenicity in animal model systems (reviewed in reference 3). The high expression level of BART miRNAs in NPC and demonstration that BART miRNAs can mediate the tumorigenicity of EBV in an animal carcinoma model system (15) is also of interest, because part of PC2 was accounted for by variation in the BART miRNA cluster 2 region (2), which is part of the long pri-miRNA (primary miRNA) transcript from which BART miRNAs are processed.…”
Section: Resultsmentioning
confidence: 99%
“…Type 2 EBV is known to be relatively more frequent in people in sub-Saharan Africa and New Guinea than other parts of the world (3). Several studies have reported type 2 EBV infection in European or U.S. populations but studied either HIV-infected people (4) or healthy subjects and did not define the ethnicity of the EBV-infected people (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is now clear that there are a large number of viral gene polymorphisms among EBV strains and that many of these are found in viral latent genes (4,5). The possibility that EBV variant strains exist that are relevant to EBV-associated diseases has started to attract interest (7,28,33). Clearly, it will be important to sequence more diseaseassociated viral genomes and to reconstitute and experimentally test such viruses in order to determine whether they behave differently from nonpathogenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing has revealed large numbers of polymorphisms in the latency-associated genes of EBV (Palser et al, 2015). Notably, a single amino acid polymorphism in EBNA2 confers more efficient immortalization of primary B-lymphocytes (Farrell, 2015), variants in LMP1 are enriched in nasopharyngeal carcinoma (NPC) (Edwards et al, 2004), deletions of EBNA2 are found in Burkitt’s lymphoma (BL) (Kelly et al, 2009), mutations in EBNA3B in Diffuse Large B cell Lymphoma (DLBCL) (White et al, 2012), and mutations in RPMS1 protein correlate with increase NPC risk (Feng et al, 2015). Viruses derived from NPC were also found to have mutations that increased spontaneous lytic reactivity and epithelial cell tropism (Tsai et al, 2013).…”
Section: Genetic Diversity: Strains and Polymorphismsmentioning
confidence: 99%